Validity of the Birchwood insight scale in patients with schizophrenia spectrum- and bipolar disorders. (February 2019) - Büchmann, Camilla Bakkalia; Pedersen, Geir; Aminoff, Sofie Ragnhild; Laskemoen, Jannicke Fjæra; Barrett, Elizabeth Ann; Melle, Ingrid; Lagerberg, Trine Vik
Highlights: Findings support a three-factor subscale structure of the Insight Scale (IS). Findings support the construct validity of the IS across all three diagnostic groups. The IS total score showed good convergent validity in SCZD and BD I. The IS total score showed poor convergent validity in BD II. Abstract: The aim of this study is to investigate the validity of the Norwegian version of the Insight Scale (IS) in large and representative samples of patients with schizophrenia spectrum disorders, bipolar I disorder and bipolar II disorder. A total of 997 participants were included (schizophrenia spectrum disorders: 557; bipolar I disorder: 282; bipolar II disorder: 138). Confirmatory factor analysis was conducted to investigate the construct validity and bivariate correlational analysis was applied to investigate convergent validity. Confirmatory factor analyses indicated a reasonable model fit to the original three-factor subscale structure of the IS in all three diagnostic groups. The IS total score and its subscales correlated significantly with both the insight items in the Young Mania Rating Scale and the Positive and Negative Syndrome Scale in both schizophrenia spectrum disorders and bipolar I disorder. In the bipolar II disorder group, however, the IS subscales correlated poorly with both the observer-rated measures. Our study supports the construct validity of the IS in both schizophrenia spectrum disorder- and bipolar disorder populations. The study also demonstrates that patients' self-reports of insight correspond to observer-based single item ratings of insight in bipolar I disorder and schizophrenia spectrum disorders.